The Triangle Model: The Contribution of the Late Professor Alex H. Johnstone - Norman Reid (JSE, 2023)
Having established the key role of the working memory in understanding and that the limited capacity of the working memory controlled success in understanding, Johnstone considered the nature of chemistry and why a subject like chemistry (along with other sciences and mathematics) caused young learners so many difficulties. This led him to develop his ‘triangle model’ and this has proved to be a very useful way to guide curriculum planners and teachers to help to make a subject like chemistry more accessible to learners. In developing the triangle model, he established that it is the way the sciences are presented in typical curricula and textbooks that made the problem a major one for learners.